Mudanças geradas pelo Previne Brasil e efeitos nas práticas de trabalhadores da gestão e da assistência da atenção primária à saúde: uma análise discursiva - Medeiros, Ana Júlia Faccio de (Universidade Federal de São Carlos, 2026)
Primary Health Care (PHC) in Brazil underwent a structural change in its financing model in 2019. The Previne Brasil Program (PPB in portuguese), established by Ordinance GM/MS No. 2,979/2019, introduced significant changes in the way resources are allocated and impacted the organization of health work. This study aimed to understand the effects of this change on the work of health professionals, focusing on the contradictions and ideological elements that permeate this experience. This is a qualitative, descriptive, and analytical study, conducted through a narrative review compared with the legal framework on the subject, discursive analysis of interviews with management-level workers and thematic analysis of interviews with frontline care workers who had professional experiences before and after the implementation of PPB. Results show a historical context of underfunding of the Brazilian Unified Health System (SUS in portuguese) particularly of PHC, which, captured by a discourse of efficiency and cost containment, finds in PPB one of its main milestones for implementation. Analysis of the statements made by management-level workers confirmed criticisms of the model, even as these statements operationalized an administrative and managerialist discourse. Furthermore, analysis of interviews with frontline care workers revealed an intensification of pressure in the workplace, reduced time allocated to consultation, impairments in the quality of care, and the weakening of collective spaces, all associated with the centrality of quantitative targets and the managerial logic introduced by the new financing model. Thus, the PPB (Basic Planning Program) operates as a political-institutional device that reorganizes work processes, affecting professional autonomy, territorial ties, and workers’ mental health. It is concluded that ethical-political suffering expresses structural processes of exclusion linked to the institutional reorganization of Primary Health Care, jeopardizing fundamental principles of SUS, such as comprehensiveness, longitudinality, and equity.
Changes generated by Previne Brasil and effects on the practices of management and care workers in primary health care: a discursive analysis
Keywords: Financiamento da assistência à saúde; Atenção primária à saúde; Processo de trabalho em saúde; Angústia psicológica; Healthcare financing; Primary health care; Health work process; Psychological distress; CIENCIAS HUMANAS::PSICOLOGIA; CIENCIAS DA SAUDE::SAUDE COLETIVA; 3. Saúde e Bem-Estar